Kurikulum Pendidikan Agama Islam Sebagai Konten di SMPN 9 Mataram - Mustiadi, Adani; Wildan, Wildan; Nurhilaliati, Nurhilaliati (Jurnal Ilmiah Global Education, 2024)
The research aims to: (1) explore information about the development of standards for the content of the Islamic Religious Education curriculum at SMP Negeri 9 Mataram; (2) understand the development of standards for the Islamic Religious Education curriculum process; and (3) identifying the development of Islamic Religious Education curriculum assessment standards. This research methodology is qualitative with data collection through observation, interviews and documentation. The validity of the data is tested through careful observation, triangulation and verification. The analysis process involves data reduction, presentation, verification, and conclusions. Research findings show that at SMP Negeri 9 Mataram, the development of content standards includes the formation of extracurricular activities. Meanwhile, the development of process standards involves the implementation of a hidden curriculum, especially the role of teachers as role models. The development of assessment standards includes the integration of three aspects of assessment: attitudes, knowledge and skills, involving the role of parents.